Collective emotions and political violence: narratives of Islamist organisations in Western Europe - Clément, Maéva (New approaches to conflict analysis, 2023)
How do collective actors move from moderate politics to (violent) extremism? Faced with high risks of repression and implosion, they need to legitimate such radical change to keep members and followers committed to collective action. Drawing on the texts, audios, and videos of five Islamist organisations in the UK and Germany in the 2000s and 2010s, the book develops a transdisciplinary theoretical framework and innovative methodological approach to explore how radical changes in activism are mediated. Clément argues that political violence has to feel right, as a collective, for an organisation and its followers to move from moderate activism to (violent) extremism. She shows that organisations mediate this change by performing collective emotions in and through narrative. The book offers a provocative and nuanced account which departs from conventional interpretations of radicalisation and reminds us of the power of emotions.